The Practice of Debts and Receivables for Basic Materials in Hadith Perspective: Case Study in Pamoroh Village, Kadur District, Pamekasan Regency - Jamil, Subhal; Matnin (NUsantara Islamic Economic Journal, 2024)
The research explores the dynamics of Debt and Credit in Pamoroh village. Debt and credit in Islam is a contract in economic transactions that contains the value of ta'awun (helping each other). The practice of debt and credit in this village has aspects that are not in accordance with the pillars of the debt and credit contract, namely, the absence of ijab qobul between the two parties, as well as the provision of prices that can be said to contain elements of usury. The type of research used in this article is empirical law or in other terms called field research. with the type of approach that will be used is the legal sociology approach. The source of data for this research comes from two sources, namely, Primary and Secondary sources. in the practice of accounts payable between the spreader of goods and consumers do not meet directly. The reason for taking consumers is because they already know that the spreader of goods only carries out the mandate of the caregiver of Ponpes M. The payment period is one month. The time period is not based on an agreement. The payment process is that the distributor of goods comes to the consumer's house and collects it. The disadvantage factor lies in the possibility of damaged goods and prices that are too expensive. the practice of accounts payable for staples is not allowed because there is no agreement between the two parties in the provision of the price of the goods but there is an addition when the payment is made, it can be said that there is an element of usury because the price increase is done without any agreement at the beginning. This is called usury Jahiliyah, which is a debt that is paid more than the principal obligation